PUSAT PENGEMBANG GAME DAN OTAKU DENGAN PENDEKATAN ESTETIKA IDIOMATIK DI YOGYAKARTA - Ratnasari Widyatama Putri; Titis Srimuda Pitana; Dyah Susilowati Pradnya Paramita (ARSITEKTURA, 2016)
The planning and designing of Game Developer and Otaku Centre in Yogyakarta is caused by local game development industry progress in Indonesia, including in Yogyakarta, which is not followed by availabilty of supporting facilities in professional game development as well as the unavailability of game development industry existence signifier. Game developer and Otaku centre is game developers workspace and Otaku gathering space that provides game development industry supporting facilities and involves Otaku as game player and game creator. There are several design issues in planning and designing of game developer and Otaku centre, (1) how the space programming concept of game developer and Otaku centre could support the game developers activities and stimulate the emergence of creative ideas, and (2) how the building appearance concept could be a signifier of local game developers existence and game characters. The approach used in planning and designing is Camp idiomatic aesthetic by using rubic cube as analogy of game characters that composed through the process of deformation, distortion, and duplication of material, in this case are rubic cube and game characters. Design decisions obtained through the analysis process are the design of game developers workspaces, co-working areas for game developers beginners, community meeting rooms, local game marketing rooms, and entertainment areas accommodated in a building complex with monumental scale and dynamic form.